Utilization of Learning Space as a Learning Resource Center - Jannah, Raodhatul; Muhammad Yaumi; Herdah (IAIN Parepare, 2023)
A conducive learning situation is related to the quality of student learning. The creation of a conducive class will prevent students from feeling bored, physical fatigue and also the creation of a conducive class will provide motivation and comfort for students' learning. Learning space is the place where the teaching and learning process takes place, the place in question can be indoors, outdoors, or virtual space. Learning space is a facility that creates a learning atmosphere and supports the creation of an innovative learning ecosystem. There are four ideas that form the basis for developing future learning spaces, namely: learning by doing, context-based, interaction, and learning locations. To realize this design, a space-technology-cognitive concept was designed that combines aspects of knowledge, aspects of space or the learning environment and the use of technology as one of the smart learning designs in the future. Utilization of learning space as a learning resource center can be carried out by referring to five functions, namely: the function of developing instructional systems; learning media service function; learning media development function; training function and administrative function.